ELighthouse: Enhance Solar Power Coverage in Renewable Sensor Networks. (7th November 2013) - Liu, Peng; Wu, Yifan; Qiu, Jian; Dai, Guojun; Fu, Tingting
Energy harvesting from ambient resource such as solar power improves the sustainability and continuous monitoring capability of sensor nodes. However, energy conservation and harvesting can hardly provide a complete solution due to two main reasons: the energy harvesting capabilities/opportunities are seriously affected by spatial and temporal facts regarding the location of sensor deployment, and distributed processing of sensing and communication are also uneven throughout the network which leads to unbalanced energy consumption. In this paper, we propose an energy transfer system called eLighthouse to level the energy harvesting and consumption of solar-powered WSN. An energy-hub equipment has been brought forward utilizing a controlled retroreflector to forward sunlight to the appropriate nodes which urgently require recharging. The scheduling algorithm among multiple nodes is also included in this paper which helps to maintain the maximum number of nodes in active state; the localization algorithm which enables the controlled retroreflector for pointing correctly is also a key contribution of this paper. The experimental and simulation results both demonstrated that the proposed system can maximize the utilization of the solar power charging technique effectively to prolong the network lifetime and build up a sustainable WSN.